Hedonic Price Model for Condominiums in Bangkok and its Vicinity - Suwannaart, Nuntawat; Jantarakolica, Korbkul; Sukhaparamate, Supawat; Suwannoi, Thanomsak; Jantarakolica, Tatree (Rajapark Journal, 2022)
The purpose of this research was to study condominium prices in Bangkok and its vicinities with different caused by factors of location, commute, privacy, and luxury. This research used a quantitative research method by collecting data by surveying the area directly from the source, divided by the level of condominiums, all 210 projects. The results showed that the location factor in the heart of the business district is increasing in condominium prices. Significantly, as a result, the price increased to 66,954.33 baht/square meter from 41,378.26 baht/square meter. The privacy factor, which is the total number of rooms in the project, every 100 units, affects the decrease in condominium prices. Significantly, as a result, the price was reduced to 40,952.41 baht/square meter from 41,378.26 baht/square meter. common value factor, resulting in increasing ice. Significantly, as a result, condominium prices will increase to 41,849.12 baht per/square meter from 41,378.26 baht/square meter. Project factors include automatic parking. As a result, condominium prices will increase to 58,396.48 baht/square meter from 41,378.26 baht/square meter. In this research, it was found that the price range obtained from the research was the criteria for determining the price of condominiums. that property developers use as a criterion for determining price competition Compare factors based on location, commute, privacy, and luxury.